2022
DOI: 10.3389/fpsyg.2021.732246
|View full text |Cite
|
Sign up to set email alerts
|

Through the Looking Glass: A Scoping Review of Cinema and Video Therapy

Abstract: Background: Cinematherapy and video treatments are artistic therapeutic techniques by which the individuals are exposed to their psycho-physical difficulties through the stories of the characters on the screen who are coping with the same issues that the patients are. Although these techniques are increasingly common within modern art therapies, there are neither comprehensive classifications of the different approaches nor agreement on their effectiveness. We performed a scoping review, describing different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
0
5
0
3
Order By: Relevance
“…The same article by Sacilotto [29] showed that films help couples to become more conscious about their problems and speak more positively about them. In line with those studies, our research confirmed that patients experiment with significant changes in dyadic satisfaction and cohesion subscales of the DAS test.…”
Section: Discussionmentioning
confidence: 97%
“…The same article by Sacilotto [29] showed that films help couples to become more conscious about their problems and speak more positively about them. In line with those studies, our research confirmed that patients experiment with significant changes in dyadic satisfaction and cohesion subscales of the DAS test.…”
Section: Discussionmentioning
confidence: 97%
“…The process of watching the film may have a direct healing effect on the patient or could become a starting point for further therapeutic interventions (Berg-Cross et al, 1990). When dealing in particular with severe mental conditions such as schizophrenia, cinema therapy has been proved only as a way for the therapy session to become more efficient thanks to the relaxation induced to the patient by a certain film, but the sole watching experience was not proved to be enough for the patient to improve (Sacilotto et al, 2022).…”
Section: Cinema Therapymentioning
confidence: 99%
“…Cinema and video therapy are sometimes used as a part of psychotherapy [3]. Therapists might use this type of therapy to expose you to a character who might be having a similar emotional experience, according to a 2021 study [4]. It could also encourage you to look at your situation from a different perspective, providing new ways of coping.…”
Section: Emotional and Mental Health Benefitsmentioning
confidence: 99%